Addressing mental and physical well-being in maritime education for future seafarers - Tri Cahyadi; Winarno Winarno; Chanra Purnama; Riyanto Riyanto; Larsen Barasa; Marudut Bernadtua Simanjuntak (Physical Therapy Journal of Indonesia, 2025)
Background: This study addresses gaps in maritime education by focusing on integrating sustainability, health management, and competency development, driven by the increasing global emphasis on sustainable operations and the mental and physical demands on seafarers. Uniquely examining the effectiveness of current curricula in meeting these emerging needs, this research provides fresh insights into their integration and highlights areas for improvement. The primary objectives were to explore the extent of this integration and assess whether current training adequately prepares students for evolving industry demands, particularly in environmental sustainability and mental health management. Methods: To investigate the integration of sustainability, health management, and competency development within maritime education, this study adopted a qualitative methodology. We conducted semi-structured interviews with five experienced lecturers and 25 recent graduates, gathering their insights and experiences. The interview data was then analyzed using thematic analysis, with cross-group comparisons to highlight differing perspectives. Alongside the interviews, observational notes and audio recordings were used to enrich the data. This approach allowed us to evaluate the efficacy of current training programs in preparing future seafarers, pinpointing areas for improvement and suggesting practical recommendations Results: The findings indicated that although maritime education effectively develops technical competencies, there are significant gaps in the integration of sustainability and health management. Both lecturers and graduates emphasized the need for more practical sustainability training and enhanced mental health support. While competency development was generally rated positively, participants called for curricula to adapt to emerging maritime technologies. Conclusion: This research underscores the necessity of evolving maritime education to better equip future seafarers for the industry's environmental and psychological demands. Recommendations include strengthening the integration of sustainability and mental health support within the curriculum, as well as ensuring that training remains current with technological advancements in the maritime sector.